2020
DOI: 10.3390/medicines7100066
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Juice Extract Decreases Cisplatin Toxicity on Peripheral Blood Mononuclear Cells

Abstract: Background: Lung cancer is one of the most prevalent cancers worldwide. Chemotherapy regimens, targeted against lung cancer, are considered an effective treatment; albeit with multiple fatal side effects. An alternative strategy, nowadays, is using natural products. Medicinal plants have been used, in combination with chemotherapy, to ameliorate side effects. Aims: This study aims to investigate the antitumor effect of pomegranate juice (Punica granatum) on human lung adenocarcinoma basal epithelial cells (A54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…In addition, the expression of N-Cadherin, Golgi phosphoprotein 3, matrix metalloproteinase-2, and matrix metalloproteinase-9 decreased. Similarly, Nasser et al [133] investigated the antitumor effect of pomegranate juice on human lung adenocarcinoma basal epithelial cells (A549). These authors reported that the treatment of A549 cells with pomegranate juice, which had a high content in flavonoids and non-flavonoid phenolic compounds, produced a decrease in the viability of these cells in a concentration-dependent manner.…”
Section: Pomegranatementioning
confidence: 99%
“…In addition, the expression of N-Cadherin, Golgi phosphoprotein 3, matrix metalloproteinase-2, and matrix metalloproteinase-9 decreased. Similarly, Nasser et al [133] investigated the antitumor effect of pomegranate juice on human lung adenocarcinoma basal epithelial cells (A549). These authors reported that the treatment of A549 cells with pomegranate juice, which had a high content in flavonoids and non-flavonoid phenolic compounds, produced a decrease in the viability of these cells in a concentration-dependent manner.…”
Section: Pomegranatementioning
confidence: 99%
“…Although few studies have reported that PE protects against CISP-induced toxicity [ 19 , 42 ], a number of other studies have shown that PE offers no protection against CISP-induced nephrotoxicity [ 5 , 14 , 21 , 32 ], and this may be due to the poor solubility. Hence, in this study, PE-NPs formulation was observed to improve its efficacy by enhancing the solubility.…”
Section: Discussionmentioning
confidence: 99%
“…Some alkaloids are known to have an effect in both phases of the formalin test [ 21 ]. In this context, we think that the short effect in phase 1 can be explained because pomegranate peel and pomegranate juice have some alkaloids like caffeine, peelletierine, and punigranate (a pyrrolidine type alkaloid), although they are not considered rich in these compounds [ 22 , 23 , 24 ]. Previous reports indicate that pomegranate peel of the Sefri variety has pain inhibition percentages (IPI) like ours (4 to 8.9%), but not the peel of the Amrouz variety, which achieved inhibition percentages of 37 to 75% (at doses of 25, 50, and 100 mg/kg intraperitoneal weight before injection of 20 µL of 2% formalin) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%